A reality check(list) for digital methods. (November 2018) - Venturini, Tommaso; Bounegru, Liliana; Gray, Jonathan; Rogers, Richard
Digital Methods can be defined as the repurposing of the inscriptions generated by digital media for the study of collective phenomena. The strength of these methods comes from their capacity to take advantage of the data and computational capacities of online platforms; their weakness comes from the difficulty to separate the phenomena that they investigate from the features of the media in which they manifest ('the medium is the message', according to McLuhan's 1964 dictum). In this article, we discuss various methodological difficulties deriving from the lack of separation between medium and message and propose eight practical precautions to deal with it.